Counseling in the Processing of Catfish Into Catfish Nuggets - Ade Vera Yani; Dasir Dasir; Idealistuti Idealistuti; Suyatno Suyatno; Khusnul Khotimah; Khairunnisa Br Tamba (Universitas Muhammadiyah Palembang, 2023)
Catfish is a fish that is well known in the community and has high nutritional value. Plaju Darat Village, Plaju District is a city in Palembang where many people raise catfish. Catfish are generally processed into catfish pecel or catfish mangut. The implementation of this service activity aims to increase the potential of catfish and diversify processed catfish. The service method is carried out by counseling and accompanied by the practice of making catfish nuggets. The results obtained from this service increase the knowledge and skills of processing catfish into catfish nuggets. It is hoped that the catfish farming community in Plaju Darat Village, Plaju District, can implement their knowledge and skills to increase the added value of catfish into catfish nuggets and increase family income.